Stress State of an Inhomogeneous Elastic Layer Made of Heterogeneous Materials with a Coin-Like Rigid Inclusion under Torsion - Gasparyan, Anush; Melkonyan, Avetik; Davtyan, Zaven (Key engineering materials, 2019)
Problems on cracks and inclusions closely relate to problems of determination of the stress-strain state of homogeneous and inhomogeneous elastic solids that contain stress concentrators. Due to their theoretical and practical importance to the issues of construction structures, machines and their parts in machinery, in the calculation of hydro-technical structures as well as in various other spheres of applied mechanics, these problems have become a subject of investigation for many authors. This paper studies the problem of determination of the stress-strain state of a piecewise homogeneous elastic layer under torsion. The upper and lower surfaces of the compound layer are loaded with tangential forces and the interface of the heterogeneous layers contains a thin absolutely rigid coin-like inclusion. It is required to determine stress jumps on the boundary of the inclusion as well as intensity coefficients of the stresses (ICS).